1990
DOI: 10.1128/mcb.10.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Active beta-globin gene transcription occurs in methylated, DNase I-resistant chromatin of nonerythroid chicken cells.

Abstract: The nature and function of the transcriptionally competent state of chromatin remains an enigma despite much work. Two properties are generally characteristic of competent chromatin: an increased sensitivity to digestion by DNase I and a reduced frequency of cytosine methylation at CpG positions (63). However, the notion of "competent" chromatin is poorly defined. Generally it is taken to mean a region of chromatin that is committed, by virtue of a special conformation, to the present or future transcription o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Cytosine methylation in the region 5 H of the chicken adult b-globin gene conforms, in general, to a pattern of hypermethylation where the gene is inactive and hypomethylation where the gene is active (Ginder & McGhee, 1981;Ginder et al, 1983;Groudine & Conkin, 1985;Lois et al, 1990). These studies, which have concentrated on the methylation status at HpaII sites, have also revealed that this pattern is not all-encompassing (see below).…”
Section: Methylation At the Cpg Triplet Motif Is Developmentally Modumentioning
confidence: 88%
“…Cytosine methylation in the region 5 H of the chicken adult b-globin gene conforms, in general, to a pattern of hypermethylation where the gene is inactive and hypomethylation where the gene is active (Ginder & McGhee, 1981;Ginder et al, 1983;Groudine & Conkin, 1985;Lois et al, 1990). These studies, which have concentrated on the methylation status at HpaII sites, have also revealed that this pattern is not all-encompassing (see below).…”
Section: Methylation At the Cpg Triplet Motif Is Developmentally Modumentioning
confidence: 88%
“…However, methyl filtration and similar approaches such as PstI cloning are based on the assumption that hypermethylated sequences represent DNA that is nongenic whereas hypomethylated sequences represent low-copy DNA. In most (if not all) instances, using cloning/sequencing techniques centered on differential sequence methylation will result in the loss of many important and interesting genes: (1) it is common knowledge that methylation is one of the primary means by which genes are regulated, and that the methylation status of genes (or portions of genes) differs markedly between tissues and/or developmental stages (Siegfried and Cedar 1997;Heslop-Harrison 2000), (2) some genes are normally active when hypermethylated (Lois et al 1990;Wölfl et al 1991;HeslopHarrison 2000) and may not function if they are demethylated (Li et al 1993), (3) in some genes methylation at one site enhances transcription whereas methylation at another site reduces transcription (Li et al 1993;Riesewijk et al 1996), and (4) some species normally possess hypermethylated genes and hypomethylated repeat sequences (Simmen et al 1999).…”
Section: Capture Of Sequence Complexity Using Cot-based Cloning and Smentioning
confidence: 99%
“…Repetitive DNA is often more highly methylated than lowcopy DNA, and consequently some researchers have used methylation-sensitive restriction enzymes (e.g., McCouch et al 1988) or bacterial host strains that preferentially restrict methylated DNA (Rabinowicz et al 1999) to produce genomic libraries enriched in low-copy (ostensibly genic) DNA. However, cloning strategies involving the preferential exclusion of hypermethylated DNA may result in the loss of important/ interesting genes because the pattern and significance of DNA methylation can differ markedly between species (e.g., Simmen et al 1999), genes within an organism (e.g., Lois et al 1990;Wölfl et al 1991), developmental stages (for review, see Heslop-Harrison 2000), and different regions of the same gene (e.g., Li et al 1993;Riesewijk et al 1996). Clearly, alternative strategies for isolating and sequencing the unique elements of genomes are needed.…”
mentioning
confidence: 99%
“…Examples of RNA polymerase II genes which are controlled at the level of transcription elongation include proto-oncogenes c-myc, c-fos, c-myb, L-myc, and N-myc (2,12,26,36,37,57), the human adenosine deaminase gene (10), the epidermal growth factor receptor gene (14), the 13-globin gene (30), the Drosophila hsp7O gene (28,46), and a number of genes of viruses such as the human immunodeficiency virus (HIV) (22,27), adenovirus (25), simian virus 40 (43), and polyomavirus (50). For reviews, see references 23 and 53.…”
mentioning
confidence: 99%